Epilepsi bangkitan umum tonik-klonik di UGD RSUP Sanglah Denpasar-Bali - Andre Kristanto (DiscoverSys Inc., 2017)
Introduction: Epilepsy is a neurological disease that is characterized by episodes of seizures which can be accompanied by loss of consciousness of the patient. Although it is usually accompanied by loss of consciousness, there are several types of seizures without loss of consciousness. The disease is caused by the instability of electrical charges in the brain which in turn interfere with muscle coordination and manifest in muscle stiffness or repetitive pounding on the muscle. Classification of epileptic seizure according to ILAE 1981 include some general seizures, partial / focal seizures, and not classified seizures. Case: A 57-year-old woman, Balinese, come to the ER with complaints a limp, escorted by residents because of fainting. Patients do not know what happened so he brought the ER. Patients know who she is, what's her name, where she was, and the current time. Patient say she felt a little dizziness, no nausea, no vomiting. Patients are found to fall unconscious. At that time the patient was at work with his daily activity carrying stuff. Before fainting said patient lying at the scene while stamping hands and feet. Not checked how long the patient was lying. From families were dropping, the patient has a history of epilepsy, had been hospitalized in the hospital with a diagnosis of epilepsy, but never control the drug after the return of hospitalization.